The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/zaac.201900319
|View full text |Cite
|
Sign up to set email alerts
|

Similarities of Coordination Polymer and Dimeric Complex of Europium(III) with Joint and Separate Terpyridine and Benzoate

Abstract: A dimeric complex of trivalent europium [Eu2Cl4(bc)2(ptpy)2] (1), containing the separate ligands 4'‐phenyl‐2,2':6',2''‐terpyridine (ptpy) and benzoate (bc–) and a one‐dimensional double strand coordination polymer of the composition 1∞[EuCl2(cptpy)] (2) with 4‐[2,2':6',2''‐terpyridin]‐4'‐yl‐benzoate (cptpy–) were obtained. The products exhibit structural similarities despite the character of joint and separate functionality of the ligands. The dimer 1 shows photoluminescence with high quantum yield [61(2) %].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…9, right), and are consistent with the literature. Indeed, the emission lifetimes are occasionally reported to be > 1.0 ms for other Eu 3+ - and Tb 3+ -containing coordination polymers, 86,87 but values of several hundred μs are generally encountered. 88–91…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9, right), and are consistent with the literature. Indeed, the emission lifetimes are occasionally reported to be > 1.0 ms for other Eu 3+ - and Tb 3+ -containing coordination polymers, 86,87 but values of several hundred μs are generally encountered. 88–91…”
Section: Resultsmentioning
confidence: 99%
“…9, right), and are consistent with the literature. Indeed, the emission lifetimes are occasionally reported to be > 1.0 ms for other Eu 3+ -and Tb 3+containing coordination polymers, 86,87 but values of several hundred µs are generally encountered. [88][89][90][91] The absorption, excitation and emission spectra and the emission decays of the Dy-Cy and Er-Cy networks at 298 and 77 K are shown in Fig.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…It was found that the sum concentration of trivalent lanthanides influences the retardation factor of individual Ln 3+ complexes formed (SI Figure S20). As trivalent lanthanides can form coordination compounds with different Ln 3+ :terpyridine ratios from 2:1 to 1:3, different species can be also formed during a TLC process. At a higher amount of Eu 3+ /Tb 3+ applied on the plate, the retardation factor of formed highly luminescent species is close to 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ptpy can be easily obtained on a gram scale at room temperature, it is water-stable, thermally stable, and stable vs air . Although terpyridine derivatives are known for decades to form highly luminescent coordination compounds with Eu 3+ and Tb 3+ , they were neither considered in detection schemes of trivalent lanthanides, nor for recovery concepts, until now. Combined with the typically intense and characteristic Eu 3+ and Tb 3+ luminescence in the visible region, it is possible to detect these ions in the aqueous solution “on the fly” within parts of a second, without the use of a spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, Eu 3+ complexes with ptpy [EuCl 3 (ptpy)(L)] (L=pyridine, acetamide) and [Eu 2 Cl 6 (ptpy) 2 (4,4’‐bipy)] ⋅ 4,4’‐bipy first release co‐coordinated organic molecules (L or 4,4’‐bipy) at 250–295 °C, with the resulting residue EuCl 3 (ptpy) being stable up to 435–445 °C [47] . In the another example, [Eu 2 Cl 4 (bc) 2 (ptpy) 2 ] is stable up to 395 °C, where a carboxylate group is responsible for the start of the decomposition [48] . As can be seen, [ScCl 3 (ptpy)] has a higher thermal stability than the Eu 3+ complexes with ptpy.…”
Section: Resultsmentioning
confidence: 99%